Of principle, practicality, and precedents: The presumption of the Arbitration Agreement’s governing law - YOONG, Aaron (Institutional Knowledge at Singapore Management University, 2021)
The issue of determining the appropriate law governing an arbitration agreement is one that has long vexed the courts in many jurisdictions. Most recently, both the English and Singapore Court of Appeals have waded into the fray, contributing contrary opinions in their respective decisions of Enka Insaat Ve Sanayi AS v OOO “Insurance Company Chubb” and BNA v BNB. This article examines these decisions and argues that there should be a presumption that the governing law of the arbitration agreement follows the matrix contract within which it is situated.